Telling Tales: Storytelling in Contemporary Spain. - Anne L. Walsh (Cambridge Scholars Publishing, 2015)
This volume delves deeply into the role played by stories and storytelling in shaping, controlling and mapping present-day Spain, and examines fiction in various manifestations and genres, especially written and filmic. It contrasts such stories and their context with the past, investigating the differences and similarities between spatially and geographically varying narrations in order to tease out the link between the time of telling and the act of living. Throughout the book, scholars look separately at this phenomenon, and their findings reveal a close bond between events occurring in the real world and the relating of fictional stories. Particularly in Spain, the geographic space of interest here, storytelling is used both as catharsis and didactically. Authors and filmmakers find inspiration in everyday occurrences, and, while there is nothing unusual in that, the interest here lies in the consequent transformation of these occurrences into fascinating stories that attempt to make sense of chaotic events, connect those events temporally, and explore the meaning of the consequent coherence. Stories are at the very essence of humanity, be they fictional or based on everyday reality. This collection focuses specifically on Spain where easily identifiable features of history (such as the Spanish Civil War, the Franco Dictatorship, transition, democracy, and the global economic crisis) have had a major impact on everyday life. The narratives emerging show clear evidence of that impact, with an emphasis on such themes as the significance of memory, the impossibility and instability of such memory, the chaotic nature of life, and the place of the nation/state in the psyche of the individual, with emerging themes investigating the role of solidarity and empathy in the empowerment of the individual. This volume is informed by the shift that.